2018
DOI: 10.1016/j.biochi.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Mesenchymal Stem Cells and their secretome as a treatment for gliomas

Abstract: In recent years, we have witnessed a significant increase in the amount of studies using Mesenchymal Stem Cells (MSCs) for cancer therapy, mostly as vectors for drug or gene delivery strategies. This is because of their intrinsic capacity of homing into tumor niches. However, the interactions between MSCs themselves and tumor cells is not fully understood, with contradictory results frequently being observed regarding their effects on cancer cell invasion and proliferation. This poses an important question of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…Moreover, the major obstacle in the clinical application of stem cells is the possibility of malignant transformation 2728293031. Meanwhile, accumulating evidence has indicated that secretome released from stem cells exhibits similar potential as stem cells because the principal action of stem cells is mediated by the secretome 3233343536373839. Our previous experiments using secretome also demonstrated that secretome has similar, at least not inferior, therapeutic potential as stem cells in ameliorating hepatic failure 171819202140…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the major obstacle in the clinical application of stem cells is the possibility of malignant transformation 2728293031. Meanwhile, accumulating evidence has indicated that secretome released from stem cells exhibits similar potential as stem cells because the principal action of stem cells is mediated by the secretome 3233343536373839. Our previous experiments using secretome also demonstrated that secretome has similar, at least not inferior, therapeutic potential as stem cells in ameliorating hepatic failure 171819202140…”
Section: Discussionmentioning
confidence: 91%
“…Walker et al 40 showed that vimentin mediates the transition of mesenchymal leader cells to a myofibroblast phenotype, facilitating fibrosis in wound repair, while vimentin deficiency resulted in a blunted inflammatory response. Vimentin is also a key regulator of the NLRP3 inflammasome, promoting lung inflammation and fibrosis 13 . In addition, PTX3 inhibits inflammation and leukocyte adhesion and transmigration 41 .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome safety concerns, several researchers have turned to their attention to the secretome, which are the molecules that are secreted or surface-shed by stem cells 8,9 . Numerous studies have demonstrated that the secretome has similar potential to that of stem cells because the principal mechanism of action of these cells is mediated by the secretome [10][11][12][13][14][15][16][17] . We have also performed several experiments that validated the therapeutic potential of the secretome, especially for the treatment of liver diseases, and have concluded that the secretome and stem cells have similar therapeutic potential, at least for improving hepatic failure [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…bone marrow, adipose tissue, umbilical cord blood and tumour tissue, and the phenotype of glioma cells, used for studies. The timing and mode of MSC administration to animal models may affect the interactions between MSCs and glioma in vitro deepening on the mode of interactions [26,73,79]. Further investigations are needed to deepen our understanding of the mechanisms of MSC behaviour in tumour microenvironment and their effects on glioma pathobiology before to successful MSC-based anti-cancer therapy will be developed.…”
Section: Heterotypic Interaction Cell Interactions In Animal Modelsmentioning
confidence: 99%